Good Mzungu? Whiteness and white supremacy in postcolonial Uganda - Christian, Michelle; Namaganda, Assumpta (Informa UK Limited, 2022)
Scholars looking at whiteness through a postcolonial lens have notably explored the lingering and multi-faceted nature of whiteness in the wake of empire. We apply Shome’s argument that whiteness is rendered visible through how it is ‘disembodied’ to explore how whiteness is signified and interpreted in a postcolonial Ugandan context and with the term Mzungu. Disembodied whiteness centres the discursive and material forms of whiteness. Interview and focus group data from domestic workers who work for foreigners in Uganda are analyzed. We argue in Uganda whiteness is structurally present in the growth of the development aid state and discursively understood in contrast and relation to Africanness and Blackness. Whiteness, Mzungu, African, Black represents multiple understandings and a duality for the Ugandan domestic workers who work in the foreign households of the aid state. Ultimately, postcolonial whiteness in Uganda sustains white supremacy, but fissures, contestation, and disruption also follow its production.